Development of an RP-UHPLC-PDA method for quantification of free gossypol in cottonseed cake and fungal-treated cottonseed cake. - Aparecido Almeida Conceição; Clemente Batista Soares Neto; José Antônio de Aquino Ribeiro; Felix Gonçalves de Siqueira; Robert Neil Gerard Miller; Simone Mendonça (PLoS ONE, 2018)
Cottonseed cake biomass, which is a residue of oil extraction, is potentially appropriate for use as animal feed, given the high mineral, fibre and protein content. The presence of free gossypol, however, a toxic pigment in the glands of the cotton plant, limits use of this biomass for monogastric livestock. A promising method to detoxify cottonseed cake relies on fermentation by fungi, which can eliminate up to 100% of gossypol. In order to quantify trace levels of free gossypol in different cotton materials, including cottonseed cake treated with macrofungi, a simple and rapid chromatographic detection method was developed and validated. Under optimized conditions, extraction was performed using 70% acetone. The extract was then analysed by Ultra High-Performance Liquid Chromatography (UHPLC), with gradient elution on a C18 reverse phase column KINETEX® (100 x 2.10 mm, 2.6 μm). Methanol-0.1% TFA aqueous solution was employed as mobile phase and PDA detection conducted at 254 nm. The optimized method was validated by analysis of specificity, linearity and range, limit of detection, limit of quantification, precision and accuracy. Detection and quantification limits were observed at 0.2 and 0.5 μg/mL, respectively. With good reproducibility, with precision (RSD)<10% and recovery greater than 94%, the developed assay was appropriate for quantification of low quantities of free gossypol. The validated method was successfully applied to determine trace levels of free gossypol cottonseed treated with a macrofungus.